Commissioning and early experiments of the PHELIX facility - Bagnoud, Vincent; Aurand, B.; Blazevic, A.; Borneis, S.; Bruske, C.; Ecker, B.; Eisenbarth, U.; Fils, J.; Frank, A.; Gaul, E.; Goette, S.; Haefner, C.; et al. (Applied physics. B, Lasers and optics, 2010)
At the Helmholtz center GSI, PHELIX (Petawatt High Energy Laser for heavy Ion eXperiments) has been commissioned for operation in stand-alone mode and, in combination with ions accelerated up to an energy of 13 MeV/u by the heavy ion accelerator UNILAC. The combination of PHELIX with the heavy-ion beams available at GSI enables a large variety of unique experiments. Novel research opportunities are spanning from the study of ion-matter interaction, through challenging new experiments in atomic physics, nuclear physics, and astrophysics, into the field of relativistic plasma physics.